2022
DOI: 10.1177/00031348221078986
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Does Not Increase Risk for Mortality in Severe Sepsis Trauma Patients

Abstract: Introduction The prevalence of obesity in the United States is up to 40% in adults. Obese patients with severe sepsis have a lower mortality rate compared with normal body mass index (BMI) patients. We hypothesized that trauma patients with severe sepsis and obese BMI will have a decreased mortality risk in comparison with normal BMI patients. Methods The Trauma Quality Improvement Program (2017) was queried for adult trauma patients with documented BMI and severe sepsis. Patients were grouped based on BMI: no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…A total of 3865 records were identified via a systematic search of databases published before March 28, 2023, and screened for inclusion based on eligibility criteria. After reviewing the titles and abstracts, 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] were selected for inclusion in this study. Specifically, these studies reported on the association between obesity and sepsis prognosis, with 8 [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , 23 ] of them focusing on overweight patients and 6 [ 14 , 16 , 18 , 20 , 21 , 35 ] of them restricting the analysis to patients with low weight.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3865 records were identified via a systematic search of databases published before March 28, 2023, and screened for inclusion based on eligibility criteria. After reviewing the titles and abstracts, 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] were selected for inclusion in this study. Specifically, these studies reported on the association between obesity and sepsis prognosis, with 8 [ 14 , [16] , [17] , [18] , [19] , [20] , [21] , 23 ] of them focusing on overweight patients and 6 [ 14 , 16 , 18 , 20 , 21 , 35 ] of them restricting the analysis to patients with low weight.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis comprised 12 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] encompassing data from multiple countries or regions with a total of 521,207 individuals, and two of which were prospective cohort studies. The follow-up time varied across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest the study by Tay-Lasso et al regarding the impact of obese body habitus on outcomes in trauma patients with severe sepsis. 1 This study offers impactful findings with a thoughtful discussion of the potential influence of these findings. We commend the authors’ contributions through their excellent efforts in exploring a crucial topic in trauma research.…”
mentioning
confidence: 90%